Clinicopathologic features, management and outcomes of blastoid variant of mantle cell lymphoma: a Nebraska Lymphoma Study Group Experience. Issue 6 (2nd June 2016) - Bhatt, Vijaya R.; Loberiza, Fausto R.; Smith, Lynette M.; Armitage, James O.; Greiner, Timothy C.; Bast, Martin; Lunning, Matthew A.; Bierman, Philip J.; Vose, Julie M.; Bociek, R. Gregory
Abstract: The objective of this retrospective study ( N  = 169) was to compare the overall survival (OS) of different subtypes of mantle cell lymphoma (MCL) treated by the Nebraska Lymphoma Study Group between 1984 and 2012. The overall response rate to various therapies including stem cell transplant (SCT) was similar ( p  = 0.44) between blastoid, diffuse and nodular subtypes. At 5 years, blastoid and diffuse subtypes had worse OS (overall p  = 0.005) compared to nodular subtype. In multivariate analysis, the blastoid and diffuse subtypes had similar risk of death ( p  = 0.14) whereas the nodular subtype had a lower risk compared to blastoid (HR 0.48, 95% CI 0.27–0.87, p  = 0.01). The use of SCT was associated with lower risk of death. In univariate analysis, blastoid subtype had better OS with intensive upfront therapy. In conclusion, the OS of blastoid subtype is worse than nodular MCL but may improve with the use of SCT and probably intensive induction therapy.